CURRENT DEVELOPMENTS AT THE SEC. - Cohen, Manuel F. (The Accounting Review, 1965)
This article discuss the U.S. Securities and Exchange Commission's (SEC) current activities and goals as they relate to the accounting profession. The Report of the Special Study of Securities Markets was sent to the U.S. Congress, its 175 conclusions and recommendations covered almost every aspect of the securities industry. Since then, the difficult task of implementing the Study recommendations has preempted much of the SEC's time and energy. With the aid of the industry, one have made significant progress. One of the most important achievements was the formulation of the legislation recently passed by the Congress and now known as the Securities Acts Amendments of 1964. Under the new law, many accountants will, for the first time, be faced with problems under the federal securities laws. One should consider it particularly appropriate, therefore, to refer to certain of the new provisions which will be of particular interest to members of accounting profession. The 1964 Amendments deal chiefly with issues of securities traded in the over-the- counter market and the standards of broker dealer firms and their salesman.